Efficient CRISPR/Cas9-Mediated Mutagenesis in Primary Murine T Lymphocytes: CRISPR-mediated gene-disruption in murine T cells - Huang, Bonnie (Curr Protoc Immunol, 2018)
The ability to alter gene expression directly in T lymphocytes has provided a powerful tool for understanding T cell biology, signaling and function. Manipulation of T cell clones and primary T cells has been accomplished primarily through overexpression or gene-silencing studies using cDNAs or shRNAs, respectively, which are often delivered by retroviral or lentiviral transduction or direct transfection methods. The recent development of CRISPR/Cas9-based mutagenesis has revolutionized genomic editing, allowing unprecedented genetic manipulation on many cell types with greater precision and ease. In this chapter, we outline a protocol for CRISPR/Cas9-mediated mutagenesis in primary T lymphocytes from Cas9 transgenic mice using retroviral delivery of guide RNAs.